A fuzzy programming approach for vendor selection problem in a supply chain - Kumar, Manoj; Vrat, Prem; Shankar, Ravi (International journal of production economics, 2006)
Vendor selection problem (VSP) has been treated in this paper as a “fuzzy Multi-objective Integer Programming Vendor Selection Problem” (f-MIP_VSP) formulation that incorporates the three important goals: cost-minimization, quality-maximization and maximization of on-time-delivery-with the realistic constraints such as meeting the buyers’ demand, vendors’ capacity, vendors’ quota flexibility, etc. In the proposed model, various input parameters have been treated as vague with a linear membership function of fuzzy type. It is tested on a data set adopted from a case company. The approach provides a decision tool that facilitates the vendor selection and their quota allocation under different degrees of information vagueness in the decision parameters of a supply chain modeling.